2017
DOI: 10.3174/ajnr.a5383
|View full text |Cite
|
Sign up to set email alerts
|

T1-Weighted Dynamic Contrast-Enhanced MR Perfusion Imaging Characterizes Tumor Response to Radiation Therapy in Chordoma

Abstract: Background and Purpose Chordomas notoriously demonstrate a paucity of changes following radiation therapy on conventional MRI. We hypothesize that dynamic contrast enhanced (DCE) MR perfusion imaging parameters of chordomas would change significantly following radiation therapy. Materials and Methods Eleven pathology-proven chordoma patients who completed DCE MR perfusion imaging pre -and post-radiation therapy were enrolled. Quantitative tumor measurements were taken by two attending neuroradiologists. ROIs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…According to a previous study 27 , the volume transfer constant ( K trans ) after RT was expected to decrease by 33.5% (standard deviation 28.9%). Using paired t-tests, the required sample size was calculated to be 10 in order to have a 90% chance of finding an average of 33.5% difference at a significance level of 5% (α = 0.05, β = 0.10) (MedCalc Statistical Software version 19.1.5; MedCalc Software Ltd.).…”
Section: Methodsmentioning
confidence: 88%
“…According to a previous study 27 , the volume transfer constant ( K trans ) after RT was expected to decrease by 33.5% (standard deviation 28.9%). Using paired t-tests, the required sample size was calculated to be 10 in order to have a 90% chance of finding an average of 33.5% difference at a significance level of 5% (α = 0.05, β = 0.10) (MedCalc Statistical Software version 19.1.5; MedCalc Software Ltd.).…”
Section: Methodsmentioning
confidence: 88%
“…MR imaging is important not only for diagnosing and differentiating disease but also in predicting prognosis. 3,16,24 Among the 32 patients who did not undergo adjuvant radiation therapy in the present series, R EN and tumor blood supply were demonstrated as independent factors for PFS. Tian et al 16 and Lin et al 17 have also had similar results, which suggested that R EN was a risk factor for PFS.…”
Section: Discussionmentioning
confidence: 58%
“…In the patients who underwent .1 resection by our team, some tumors recurred as a different electron microscopic type from their previous surgical result. These findings may indicate that the tumor cells were heterogeneously arranged, 24 and the tiny amount of tissue in the electron microscopic sample may not exactly represent the whole tumor. With MR imaging analysis, the sampling error is greatly reduced because ROIs are selected by drawing the largest possible elliptic area within the tumor but avoiding areas of hemorrhage, necrosis, cyst, or calcification.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…For instance, it was proven to be helpful to discriminate different SBTs, 70,71 as well as to distinguish SBTs from infectious conditions, 72,73 and promising results were also described in the evaluation of the response to therapy. 74 Regarding spine infection, morphological features remain crucial diagnostic findings to correctly differentiate it from SBT, with, for instance, absence of disk involvement, with a paravertebral or epidural abscess typical for the latter. Nevertheless, misdiagnosis was sporadically reported in cases of tuberculosis.…”
Section: New Perspectivesmentioning
confidence: 99%